Pemberdayaan Sistem Pengawasan Independen Terhadap Proses Pemilu Sebagai Upaya Mewujudkan Demokrasi Yang Berkualitas - Pambudi, Mbareb Slamat; Farna, Nuzulluddin; Hamada, Nourismi; Saripudin, Akhmad (Universitas Muara Bungo, 2025)
The empowerment of an independent oversight system in the electoral process is crucial to achieving a high-quality democracy. Independent oversight systems, such as those implemented by Bawaslu, aim to ensure transparency, accountability, and fairness in the conduct of elections. This paper examines the roles and functions of independent electoral supervision, the challenges faced in its implementation, and strategies to strengthen its capacity in overseeing electoral processes. Through rigorous oversight, independent monitoring bodies help prevent electoral fraud, enhance public trust, and promote democratic integrity. The study concludes with recommendations to further empower independent oversight bodies and foster more democratic practices in electoral systems, thereby supporting a sustainable, high-quality democratic state.